Blockchain Technology in Managerial Accounting: Transforming Cost Management Strategies - Brar, Manvinder; Seth , Kanika; Mishra , Smita; Kumari, Dr. Sweta; Shadangi , Dr. Preeti Y; Sheeba, Dr.T.; Rao, P.S. Raghavendra (International Journal of Accounting and Economics Studies, 2025)
Accounting is the study of recording, categorizing, summarizing, and interpreting financial data regarding an organization's operations to make informed decisions about the organization. The information required to meet management goals is built on processes, which include information collection, measurement, storage, analysis, reporting, and management. Additionally, manufacturing, commerce, service, and nonprofit companies also use this kind of information; therefore, its demand is not just restricted to industrial organizations. Using a mixed-methods research approach, primary data is collected through surveys and interviews with finance professionals, blockchain experts, and business executives, while secondary data is analyzed from industry reports and financial statements of companies implementing blockchain. The study includes organizations across industries such as manufacturing, retail, and logistics that utilize blockchain for cost optimization. Key inclusion criteria focus on firms actively using blockchain in accounting, while businesses without blockchain adoption and outdated studies are excluded. Findings are analyzed using qualitative thematic analysis and quantitative statistical methods to assess cost reduction and efficiency improvements. This research highlights blockchain’s role in reshaping managerial accounting and provides insights into its challenges, such as regulatory concerns and technological adoption barriers. The study contributes to the evolving discussion on digital transformation in financial management, offering recommendations for businesses seeking to leverage blockchain for cost efficiency and strategic decision-making.